Reflections of Television's Technical Development and Identification in Turkey: Efforts to Understand Television in the 1930s - Ilaslan, Suleyman (Marmara Univ, Fac Communication, 2021)
The invention of television and its integration to daily life by completing its technical progression covers a long historical period. This period is accompanied by efforts to understand television and position it into social and cultural life. Discourses about television was not only limited to Western countries that discovered this device, but also spread to others, such as Turkey in the 1930s. The intensity of the news and columns on the development of television in newspapers during the 1930s points at the interest in this new communication technology. In this regard, this article focuses on how television was established in the public discourse in Turkey from the late 1920s to 1940s. For this purpose, this article analyzes how the identification of television in public discourse is influenced by the dominant television discourse in the countries that pioneered the invention and the development of this new technology. In terms of methodology, this article conducts a history of mentalities approach on the discourses about television, based on the period's newspaper archives. By an archival research focused on the keyword television in the National Library's digital archives through newspapers such as Aksam, Hakimiyeti Milliye, Kurun, Ulus ve Vakit, the public discourse on television in the 1930s is analyzed by a qualitative approach. As a result of the research, it has been observed that the identification of a new communication technology was realized in the context of the social conditions and the existing communication forms of the period. In addition, the international discourse on this new communication technology and form also played a fundamental role in making sense of television in Turkey.
Keywords: Communication; Technology; Television; Broadcasting; Social-Cultural Life